The Role and Efficacy of Creative Imagination in Concept Formation: A Study of Variables for Children in Primary School - Javier Gonzalez Garcia; Tirtha Prasad Mukhopadhyay (Education Sciences, 2019)
Children’s creative imagination is tested through tasks involving narrative and drawing abilities for participants between the age of 8 and 12 years. The test determines the relative importance of ‘narrative’ against ‘graphic’ imagination in interpretive, problem-solving strategies, and also considers how such distinctive functions of the creative imagination could affect ‘general’ creativity of the child learner. Participants were chosen from designated primary schools in the state of Guanajuato, Mexico. The test on creativity complements facts from observational methodology in a population of mixed Castilian-speaking children. The name of the test is Prueba de Imaginación Creativa Niños (2008) or ‘Test of Creative Imagination in Children’, the Castilian acronym being PIC-N. It comprised four sub-tests: Three designed to evaluate narrative (verbal) creativity, and one for drawing (i.e., graphic) creativity. The first three ‘exercises’ in the suite indicates (a) fluency, (b) flexibility, and (c) originality in narrative representations, whereas the fourth indexes (d) graphic abilities of the child learner. Results suggest that creative imagination causes variations in specific aspects of creativity, like narrative and graphic improvisation, and also modifies ‘general’ creativity as understood from the perspective of a developmental psychology of learning abilities in growing children within the defined age group.